Qualitative study on students' appreciation and practices toward Islamic education curriculum in selected Islamic private schools of West Kalimantan, Indonesia - Saniati, Dewi (Institute of Education, International Islamic University Malaysia, 2013)
The purpose of this study was to identify how students come to appreciate and practice the value of Islamic education curriculum. This is in response to the importance of Islamic education to develop students' Islamic morality. Another aim was to find out factors that influence students to appreciate the value of the curriculum. Finally, the difficulties and dilemmas for students to appreciate and practice the curriculum were explored in the study. This study utilised of qualitative research methodology. The data consisted of six semi-structured interviews with students of selected Islamic private schools in Pontianak, West Kalimantan, Indonesia. The findings revealed that students believe Islamic education is meaningful for it is not only a subject learnt in the class but the internalization of Islamic values as the guidance in life. Next, the interviews discovered that students describe profoundly their appreciation on the value of Islamic education in the dimension of practical worship (Ibadah) more than the dimension of Islamic belief (aqidah.) The study also confirmed that various factors including teachers, parents, Islamic school's policy and facilities help to improve students' appreciation and practice, while peer group is influenced the students either as the solution or the problem. In general, a majority of students felt that low self motivation or laziness is considerably viewed as the major dilemma for them to appreciate and practice the value of Islamic education curriculum. The researcher recommends that additional data collection for the present study through observation would enrich the subjective experience of the students. Exploring the teachers' strategies to scaffold students' appreciation toward Islamic education curriculum especially in the aspect of Islamic aqidah is also recommended.